Frontispiece: Hierarchical Tubular Structures Grown from the Gel/Liquid Interface. Issue 49 (1st December 2014) - Steenbjerg Ibsen, Casper Jon; Mikladal, Bjørn Fridur; Bjørnholt Jensen, Uffe; Birkedal, Henrik
<x xml:space="preserve">Abstract</x> Growing Mineral Tubes Three dimensional hierarchical materials are widespread in nature but are difficult to synthesize by using self‐assembly/organization. Centimeter‐long ∼100 μm diameter tubes with complex mineral wall structures have been obtained by using a gel–liquid interface through a growth mechanism akin to that of chemical gardens: the tubes grew into alkaline solutions of anions, such as PO43− or CO32−, layered on top of a gelatin gel loaded with metal cations due to the strongly driving chemical reactions across the interface. For more details, see the Full Paper by H. Birkedal et al. on page 16112 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>